MENGUKUR KUALITAS PORTAL RUMAH BELAJAR DENGAN MENGGUNAKAN METODE WEBQUAL 4.0 - Yudiastuti, Helda; Megawaty, Megawaty (Universitas Bina Darma, 2015)
The Government continues to seek the empowerment potential of the internet for educational needs. One effort that developed was to create a portal for learning, one of which is the House of learning. In this study, quality Home Study Education Portal will be measured using the WebQual method. Sample retrieval technique using a purposive sampling. Samples taken from 150 students and 50 teachers. A survey conducted by interviews and questionnaires gives implicit to the students and teachers at the high school. Multiple linear regression analysis was used to examine the relationships between the dimensions of webQual 4.0 i.e. usability, research that reached from hypothesis testing 1,2 and 3, variable Usability and Information Quality has no effect and does not significantly to the satisfaction of the user Portal Home study, it is less perceived benefits by students and teachers because they have yet to make use of the portal.